2018
DOI: 10.1090/jams/908
|View full text |Cite
|
Sign up to set email alerts
|

No occurrence obstructions in geometric complexity theory

Abstract: The permanent versus determinant conjecture is a major problem in complexity theory that is equivalent to the separation of the complexity classes VPws and VNP. Mulmuley and Sohoni [37] suggested to study a strengthened version of this conjecture over the complex numbers that amounts to separating the orbit closures of the determinant and padded permanent polynomials. In that paper it was also proposed to separate these orbit closures by exhibiting occurrence obstructions, which are irreducible representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Such λ are called occurrence obstructions. It was recently shown that no lower bounds better than dc(per m ) > m 25 can be proved with occurrence obstructions [BIP16]. Mulmuley and Sohoni proposed even further to use the following upper bound for a ′ λ (d[n]) coming from the coordinate ring of the determinant orbit: The algebraic group GL n 2 is an affine variety and acts on itself by left and right multiplication.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such λ are called occurrence obstructions. It was recently shown that no lower bounds better than dc(per m ) > m 25 can be proved with occurrence obstructions [BIP16]. Mulmuley and Sohoni proposed even further to use the following upper bound for a ′ λ (d[n]) coming from the coordinate ring of the determinant orbit: The algebraic group GL n 2 is an affine variety and acts on itself by left and right multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…4.2.7]) tells us how its coordinate ring splits as a GL n 2 ×GL n 2 -representation: C[GL n 2 ] ≃ λ V λ ⊗V λ * , where the sum is over all isomorphism types of GL n 2 and λ * is the type dual to λ. If p ∈ A n has a reductive stabilizer S ⊆ GL n 2 , then the orbit GL n 2 p is an affine variety whose coordinate ring C[GL n 2 p] is the ring of right S-invariants: C[GL n 2 p] = C[GL n 2 ] S , see [BIP16,Sec. 4.1 & 4.2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Waring rank is a classical problem in algebraic geometry and invariant theory, with pioneering work done in the second half of the 19th century by A. Clebsch, J.J. Sylvester, and T. Reye, among others [IK99,Introduction]. It has enjoyed a recent resurgence of popularity within algebraic geometry [IK99,Lan12] and has connections in computer science to the limiting exponent of matrix multiplication ω [CHI + 18], the Mulmuley-Sohoni Geometric Complexity Theory program [BIP19], and several other areas in algebraic complexity [Lan17,EGOW18]. This paper adds parameterized algorithms to this list, showing that several methods in this area (color-coding methods [AYZ95, AG07, HWZ08], the group-algebra/determinant sum approach [Kou08, Wil09,Bjö10], and inclusion-exclusion methods) fundamentally result from rank upper bounds for a specific family of polynomials.…”
Section: Introductionmentioning
confidence: 99%